1993
DOI: 10.1152/ajpcell.1993.265.3.c770
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell phospholipid distribution and phospholipase activity during acute and chronic hypoxia

Abstract: We have previously reported alterations in cyclooxygenase metabolism in cultured aortic and pulmonary arterial endothelial cells exposed to acute and chronic hypoxia. These alterations depended on the duration and degree of the hypoxic exposure, on the vascular bed from which the endothelial cells were derived, and possibly on the availability of arachidonic acid secondary to modifications in metabolic substrate, membrane phospholipids, and/or membrane phospholipase activity. To investigate this last point fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Similar to previous reports, PAEC cultured long-term in 3% oxygen proliferated, retained the characteristics associated with cultured endothelial cells, and demonstrated no evidence of cellular injury (9)(10)(11)16). …”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…Similar to previous reports, PAEC cultured long-term in 3% oxygen proliferated, retained the characteristics associated with cultured endothelial cells, and demonstrated no evidence of cellular injury (9)(10)(11)16). …”
Section: Methodssupporting
confidence: 88%
“…In addition, this is the initial study to suggest that metabolic arrest, an increasingly reported mechanism for developing hypoxia tolerance in invertebrates and lower vertebrates, may also occur in some mammalian cells. Although further studies will be necessary to confirm these suggestions and to determine whether this preservation of high energy phosphates is sufficient, in and of itself, to confer hypoxia tolerance, it is not improbable that other measures, such as the lack of plasma membrane hydrolysis ( 16) and the upregulation of a specific set of stress proteins (1 1, 21, 42), may also contribute to the ability of PAEC to tolerate acute and chronic decreases in ambient oxygen concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations